Polarization splitting prism and preparation method thereof
By setting up a multi-layer film system on the light-transmission surface of the Gran prism, the interference effect is used to improve the transmittance of the polarized spectroscopy in the ultraviolet band, and combined with materials and structures with high anti-laser damage performance, the existing technology is solved The problems of low transmittance and insufficient anti-laser damage performance have achieved the effect of high transmittance and high anti-laser damage threshold.
Patent Information
- Application Number
- CN202411556119.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-27
AI Technical Summary
The existing polarized spectroscopic prism has low transmittance in a wide wavelength range of ultraviolet and insufficient anti-laser damage performance, making it difficult to meet the requirements of high transmission and high anti-laser damage thresholds.
A polarization spectroscopic prism is designed. By setting a multi-layer film system on each light-through surface of the Glen prism body, the interference effect of the multi-layer film is used to achieve ultraviolet wide-band transparency, and high resistance to laser damage is selected. Material and structure, including a first low refractive index fluoride film, a silicon oxide film, an alumina film and a second low refractive index fluoride film arranged on the first surface, and a Corresponding resistant membrane.
It achieves high transmittance in a wide wavelength range of the ultraviolet band, while maintaining high UV anti-laser damage performance, meeting the requirements of the laser system for transmittance and anti-laser damage threshold.
Smart Images

Figure CN119200248A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical elements, and in particular to a polarization beam splitter prism and a method for preparing the same. Background Art
[0002] Polarizing beam splitter (PBS) is a special optical element used to split the incident light into two linear polarized beams with perpendicular polarizations according to different polarization directions. This type of beam splitter is widely used in optical experiments, laser technology, microscope systems, optical communications, and optical measurements. In laser systems, especially ultraviolet laser applications, polarizing beam splitters with high transmittance, high extinction ratio, and high damage threshold are required. Currently, α-BBO Glan laser prisms, optically bonded glass polarizing beam splitters, or flat plate polarizing beam splitters are more commonly used. Among them, the extinction ratio of α-BBO Glan laser prism is much higher than that of optically bonded glass polarizing beam splitters and flat plate polarizing beam splitters, so it has an irreplaceable position in ultraviolet polarizing beam splitting applications.
[0003] The α-BBO Glan laser prism is composed of two identical α-BBO prisms arranged opposite to each other, with an air gap structure in the middle and fixed with a glass sheet. The birefringence effect of the crystal is used to achieve beam splitting, so that a beam of non-polarized light becomes polarized light with a very high extinction ratio after passing through the Glan laser prism. In the application of ultraviolet laser systems, the transmittance and laser damage threshold of the Glan laser prism are also required to be as high as possible. In order to improve the transmittance and prevent surface deliquescence, an anti-reflection film is usually coated on each light-transmitting surface of the α-BBO Glan prism. However, the anti-reflection film in the prior art only enhances the transmittance of a single wavelength light beam, resulting in a low transmittance over a wider wavelength range. Summary of the invention
[0004] The purpose of the present application is to provide a polarization beam splitter prism and a method for preparing the same, which can achieve a higher transmittance within a wider ultraviolet wavelength range.
[0005] On the one hand, an embodiment of the present application provides a polarization splitter prism, including a Glan prism body, the Glan prism body including a first surface and a second surface arranged opposite to each other, a polarization splitting surface arranged between the first surface and the second surface, and a third surface arranged between the polarization splitting surface and the first surface or the second surface. Incident light enters the Glan prism body from the first surface and is separated at the polarization splitting surface to form P-polarized light and S-polarized light. The P-polarized light and the S-polarized light are emitted from the second surface and the third surface respectively. A first low-refractive-index fluoride film, a first silicon oxide film, a first aluminum oxide film, and a second low-refractive-index fluoride film are sequentially arranged on the first surface as incident anti-reflection films.
[0006] As an implementable manner, the optical thickness ratio of the first low refractive index fluoride film, the first silicon oxide film, the first aluminum oxide film and the second low refractive index fluoride film is (0.3-0.34):(1.43-1.47):(1-1.04):(0.94-0.98).
[0007] As an implementable method, a P light anti-reflection film is arranged on the polarization splitting surface, and the P light anti-reflection film includes a third low refractive index fluoride film, a second aluminum oxide film, a fourth low refractive index fluoride film, a third aluminum oxide film, a fifth low refractive index fluoride film, a first hafnium oxide film and a sixth low refractive index fluoride film arranged in sequence.
[0008] As an implementable method, the thickness ratios of the third low refractive index fluoride film, the second aluminum oxide film, the fourth low refractive index fluoride film, the third aluminum oxide film, the fifth low refractive index fluoride film, the first hafnium oxide film and the sixth low refractive index fluoride film are (0.48-0.52): (1.06-1.1): (0.48-0.52): (1-1.04): (1.21-1.25): (0.65-0.69): (0.28-0.32).
[0009] As an implementable manner, an S light anti-reflection film is disposed on the third surface, and the S light anti-reflection film includes a seventh low-refractive index fluoride film, a fourth aluminum oxide film, a second hafnium oxide film, and an eighth low-refractive index fluoride film disposed in sequence.
[0010] As an implementable manner, the optical thickness ratio of the seventh low-refractive-index fluoride film, the fourth aluminum oxide film, the second hafnium oxide film, and the eighth low-refractive-index fluoride film is (0.28-0.32):(1.72-1.76):(0.41-0.45):(1.19-1.23).
[0011] As an practicable manner, the first low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the second low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the third low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the fourth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the fifth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the sixth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the seventh low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the eighth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride.
[0012] As an implementable manner, the incident light is incident on the polarization splitting surface at an angle of θ, and the S-polarized light is incident on the third surface at an angle of 90°-2θ.
[0013] As an implementable manner, the angle θ is between 36° and 37.5°.
[0014] On the other hand, an embodiment of the present application provides a method for preparing a polarization beam splitter prism, which is used to prepare the anti-reflection film of the above-mentioned polarization beam splitter prism, comprising: wiping and cleaning the surface of the Glan prism to be coated, then placing the Glan prism body in a coating chamber of a coating machine, and evacuating the coating chamber and heating the coating chamber so that the temperature of the coating chamber is between 180-220°C; using an oxygen ion beam to clean the Glan prism body, wherein the oxygen flow rate during cleaning is between 15-25sccm; forming a first low refractive index fluoride film, a first silicon oxide film, a first aluminum oxide film and a second low refractive index fluoride film on the first surface of the Glan prism body in sequence, wherein the first low refractive index fluoride film, the first silicon oxide film and the second low refractive index fluoride film are prepared by electron beam evaporation technology, and the first aluminum oxide film is plated by electron beam evaporation reaction deposition technology; cooling to room temperature in a vacuum environment.
[0015] The beneficial effects of the embodiments of the present application include:
[0016] The polarization beam splitter prism provided by the present application includes a Glan prism body and an anti-reflection film arranged on each light-transmitting surface of the Glan prism body. The anti-reflection film is arranged with a corresponding multi-layer film system structure according to the incident angle and polarization state of each surface light, and the interference effect of the multi-layer film is utilized to realize ultraviolet wide-band anti-reflection, so that the prism can achieve high transmittance within a wide wavelength range of the ultraviolet band. The material selection, structural setting and preparation method of the anti-reflection film all take into account the requirements of high resistance to laser damage, so that while improving the transmittance, a high ultraviolet anti-laser damage performance is maintained. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 A schematic structural diagram of a Glan prism body of a polarization beam splitter prism provided in an embodiment of the present application;
[0019] Figure 2 A schematic diagram of the structure of a first film system of a polarization beam splitter prism provided in an embodiment of the present application;
[0020] Figure 3 A schematic diagram of the structure of a polarization beam splitting surface film system of a polarization beam splitting prism provided in an embodiment of the present application;
[0021] Figure 4A schematic diagram of the structure of a third film system of a polarization beam splitter prism provided in an embodiment of the present application;
[0022] Figure 5 A flow chart of a method for preparing a polarization beam splitter prism provided in an embodiment of the present application.
[0023] Icon: 110-Glan prism body; 111-first surface; 112-polarization splitting surface; 113-third surface; 114-second surface; 121-incident light; 122-P polarized light; 123-S polarized light; 131-first low refractive index fluoride film; 132-first silicon oxide film; 133-first aluminum oxide film; 134-second low refractive index fluoride film; 141-third low refractive index fluoride film; 142-second aluminum oxide film; 143-fourth low refractive index fluoride film; 144-third aluminum oxide film; 145-fifth low refractive index fluoride film; 146-first hafnium oxide film; 147-sixth low refractive index fluoride film; 151-seventh low refractive index fluoride film; 152-fourth aluminum oxide film; 153-second hafnium oxide film; 154-eighth low refractive index fluoride film. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0025] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0026] The present application embodiment provides a polarization beam splitter prism, such as Figure 1 and Figure 2As shown, the Glan prism body 110 includes a first surface 111 and a second surface 114 arranged opposite to each other, a polarization splitting surface 112 arranged between the first surface 111 and the second surface 114, and a third surface 113 arranged between the polarization splitting surface 112 and the first surface 111 or the second surface 114 and perpendicular to the first surface. The incident light 121 enters the Glan prism body 110 from the first surface 111 and is separated at the polarization splitting surface 112 to form P polarized light 122 and S polarized light 123. The P polarized light 122 and the S polarized light 123 are emitted from the second surface 114 and the third surface respectively. A first low refractive index fluoride film 131, a first silicon oxide film 132, a first aluminum oxide film 133 and a second low refractive index fluoride film 134 are sequentially arranged on the first surface 111 as incident anti-reflection films.
[0027] The polarization splitter prism provided in the embodiment of the present application includes a Glan prism body 110. The Glan prism body 110 utilizes its own birefringence effect to separate the o-light and the e-light in the incident light 121, so that the non-polarized light incident on the second surface 114 at an appropriate angle will undergo different phenomena at the second surface 114, among which the o-light (S polarization) will be totally reflected and the e-light (P polarization) will be transmitted, thereby realizing polarization splitting. Specifically, the Glan prism body 110 includes a first surface 111 and a second surface 114 arranged opposite to each other, a polarization splitting surface 112 arranged between the first surface and the second surface 114, and a third surface 113 arranged between the polarization splitting surface 112 and the first surface 111 or the second surface 114. The incident light 121 enters the Glan prism body 110 from the first surface 111 and is separated at the polarization splitting surface 112 to form P-polarized light 122 and S-polarized light 123, wherein the P-polarized light 122 and the S-polarized light 123 are emitted from the third surface 113 and the polarization splitting surface 112 respectively, so as to achieve the effect of polarization splitting.
[0028] In order to improve the transmittance at the first surface 111, the embodiment of the present application sequentially arranges a first low-refractive-index fluoride film 131, a first silicon oxide film 132, a first aluminum oxide film 133 and a second low-refractive-index fluoride film 134 on the first surface 111 as incident anti-reflection films.
[0029] Specifically, the first low-refractive-index fluoride film 131 includes one of magnesium fluoride and aluminum fluoride, and the second low-refractive-index fluoride film 134 includes one of magnesium fluoride and aluminum fluoride. The low-refractive-index fluoride is a material with a relatively low refractive index among fluorides.
[0030] The specific structure and specific material of the Glan prism body 110 are not limited in the present embodiment. For example, the structure of the Glan prism body 110 is as follows: Figure 1As shown, it includes a right angle prism A and a right angle prism B of the same structure arranged opposite to each other, and the material of the two right angle prisms is α-BBO. Due to the particularity of the crystal structure, α-BBO has different effects on S polarized light and P polarized light, thereby separating S polarized light and P polarized light. Specifically, the inclined planes of the two right angle prisms are arranged opposite to each other, serving as the polarization splitting plane 112, so that the Glan prism body 110 is in the shape of a rectangular parallelepiped. Figure 1 1 and 2 show the optical path diagram of the polarization beam splitting prism, wherein the incident light 121 includes light of two polarization directions, the incident light 121 is incident from the first surface, is separated at the polarization beam splitting surface 112, and is emitted from the third surface 113 and the second surface 114.
[0031] An air gap is formed between the right angle prism A and the right angle prism B. In order to fix the positions of the right angle prism A and the right angle prism B, the following method can be used: Figure 1 The slide shown is glued in place.
[0032] When the polarization splitter prism provided in the present application realizes polarization splitting, the incident light 121 enters the Glan prism body 110 from the first surface 111. The present application arranges multiple layers of films in sequence on the first surface 111. Through the interference effect of the multiple layers of films, the first surface 111 can achieve a higher transmittance within a wider wavelength range.
[0033] Optional, such as Figure 2 As shown, the optical thickness ratios of the first low-refractive-index fluoride film 131, the first silicon oxide film 132, the first aluminum oxide film 133, and the second low-refractive-index fluoride film are (0.3-0.34):(1.43-1.47):(1-1.04):(0.94-0.98).
[0034] As can be seen from the above, interference occurs at each film layer of the first surface 111. In order to achieve higher transmittance in a wider wavelength range, in the embodiment of the present application, the optical thickness ratios of the first low refractive index fluoride film 131, the first silicon oxide film 132, the first aluminum oxide film 133 and the second low refractive index fluoride film are (0.3-0.34): (1.43-1.47): (1-1.04): (0.94-0.98).
[0035] The specific thickness ratio of each film layer is not limited in the embodiment of the present application, and those skilled in the art can set it according to actual conditions. For example, the optical thickness ratio of the first low refractive index fluoride film 131, the first silicon oxide film 132, the first aluminum oxide film 133 and the second low refractive index fluoride film is 0.32:1.45:1.02:0.96. At this time, the film structure of the incident anti-reflection film is G / 0.32L1 / 1.45L2 / 1.02M / 0.96L1 / A, wherein G represents the substrate α-BBO, L1 represents a quarter-wavelength thick MgF2 film layer, L2 represents a quarter-wavelength thick SiO2 film layer, and M represents a quarter-wavelength thick Al2O3 film layer.
[0036] In addition, the specific thickness of each film layer is also related to the design wavelength, and the physical thickness is a quarter of the design wavelength multiplied by the above optical thickness ratio, that is, the thickness of the first low-refractive-index fluoride film 131 is 0.32*(λ / 4), and the thickness of the first silicon oxide film 132 is 1.45*(λ / 4), so as to determine the specific thickness of each film layer. Since the incident light 121 has multiple wavelengths, λ here is the central wavelength of the incident light 121.
[0037] In practical applications, in order to design the thickness, material and position relationship of each film layer on the first surface 111, commonly used film system design software, such as Tfcal, Macleod, etc., can be used for design.
[0038] In one possible implementation of the embodiment of the present application, Figure 1 As shown, the incident light 121 is incident perpendicularly to the first surface 111 .
[0039] Optional, such as Figure 3 As shown, a P light anti-reflection film is arranged on the polarization splitting surface 112, and the P light anti-reflection film includes a third low refractive index fluoride film 141, a second aluminum oxide film 142, a fourth low refractive index fluoride film 143, a third aluminum oxide film 144, a fifth low refractive index fluoride film 145, a first hafnium oxide film 146 and a sixth low refractive index fluoride film 147 arranged in sequence.
[0040] In order to further increase the transmittance of the P polarized light when it is emitted, a P light anti-reflection film is disposed on the second surface 114. The arrangement of various levels of the P light anti-reflection film can increase the transmittance of the P light within a wider wavelength range.
[0041] In one implementable manner of an embodiment of the present application, the ratio of the optical thicknesses of the third low refractive index fluoride film 141, the second aluminum oxide film 142, the fourth low refractive index fluoride film 143, the third aluminum oxide film 144, the fifth low refractive index fluoride film 145, the first hafnium oxide film 146 and the sixth low refractive index fluoride film 147 is (0.48-0.52): (1.06-1.1): (0.48-0.52): (1-1.04): (1.21-1.25): (0.65-0.69): (0.28-0.32).
[0042] By setting the optical thickness ratio of each film layer within the above range, it is possible to further improve the transmittance in a wider wavelength range. In addition, the incident anti-reflection film provided in the embodiment of the present application optimizes the electric field distribution inside the film system structure, further improving the laser damage resistance of the film system, so that the polarization splitting laser as a whole has a higher ultraviolet laser damage resistance.
[0043] The specific thickness ratio of each film layer is not limited in the embodiment of the present application, and those skilled in the art can set it according to the actual situation. For example, the optical thickness ratio of the third low-refractive index fluoride film 141, the second aluminum oxide film 142, the fourth low-refractive index fluoride film 143, the third aluminum oxide film 144, the fifth low-refractive index fluoride film 145, the first hafnium oxide film 146 and the sixth low-refractive index fluoride film 147 is 0.5:1.08:0.5:1.02:1.23:0.67:0.3. At this time, the film structure of the P light anti-reflection film is G / 0.5L1 / 1.08M / 0.5L1 / 1.02M / 1.23L1 / 0.67H / 0.3L1 / A, where G represents the substrate α-BBO, L1 represents a quarter-wavelength thick MgF2 film layer, M represents a quarter-wavelength thick Al2O3 film layer, and H represents a quarter-wavelength thick HfO2 film layer.
[0044] Similar to the first surface 111 , the specific thickness of each film layer is also related to the design wavelength, and the specific physical thickness can be obtained by multiplying the above optical thickness ratio by one quarter of the wavelength.
[0045] Optional, such as Figure 4 As shown, an S light anti-reflection film is disposed on the third surface 113 , and the S light anti-reflection film includes a seventh low-refractive index fluoride film 151 , a fourth aluminum oxide film 152 , a second hafnium oxide film 153 and an eighth low-refractive index fluoride film 154 disposed in sequence.
[0046] In order to further increase the transmittance of S-polarized light when it is emitted, an S-light anti-reflection film is arranged on the third surface. The arrangement of various levels of the S-light anti-reflection film can increase the transmittance of the S-light in a wider wavelength range.
[0047] In one implementable manner of the embodiment of the present application, the optical thickness ratio of the seventh low-refractive-index fluoride film 151, the fourth aluminum oxide film 152, the second hafnium oxide film 153 and the eighth low-refractive-index fluoride film 154 is (0.28-0.32): (1.72-1.76): (0.41-0.45): (1.19-1.23).
[0048] Setting the optical thickness ratio of each film layer within the above range can further improve the transmittance in a wider wavelength range.
[0049] The specific thickness ratio of each film layer is not limited in the embodiment of the present application, and those skilled in the art can set it according to the actual situation. For example, the optical thickness ratio of the seventh low-refractive index fluoride film 151, the fourth aluminum oxide film 152, the second hafnium oxide film 153 and the eighth low-refractive index fluoride film 154 is 0.3:1.74:0.43:1.21. At this time, the film structure of the S-light anti-reflection film is G / 0.31L1 / 1.74M / 0.43H / 1.21L1 / A, where G represents the substrate α-BBO, L1 represents a quarter-wavelength thick MgF2 film layer, M represents a quarter-wavelength thick Al2O3 film layer, and H represents a quarter-wavelength thick HfO2 film layer.
[0050] Similar to the first surface 111 , the specific physical thickness of each film layer is also related to the design wavelength. The specific physical thickness can be obtained by multiplying the above optical thickness ratio by one quarter of the wavelength.
[0051] As an practicable manner, the first low refractive index fluoride film 131 includes one of magnesium fluoride and aluminum fluoride; the second low refractive index fluoride film 134 includes one of magnesium fluoride and aluminum fluoride; the third low refractive index fluoride film 141 includes one of magnesium fluoride and aluminum fluoride; the fourth low refractive index fluoride film 143 includes one of magnesium fluoride and aluminum fluoride; the fifth low refractive index fluoride film 145 includes one of magnesium fluoride and aluminum fluoride; the sixth low refractive index fluoride film 147 includes one of magnesium fluoride and aluminum fluoride; the seventh low refractive index fluoride film 151 includes one of magnesium fluoride and aluminum fluoride; and the eighth low refractive index fluoride film 154 includes one of magnesium fluoride and aluminum fluoride.
[0052] Optionally, the incident light enters the polarization splitting surface 112 at an angle of θ, and the S-polarized light enters the third surface at an angle of 90°-2θ.
[0053] When the incident light is incident perpendicularly to the first surface 111 and the angle of the right angle prism is θ, the incident light is incident on the polarization splitting surface 112 at an angle of θ, and the S polarized light is incident on the third surface at an angle of 90°-2θ, which can meet the splitting condition.
[0054] Specifically, the angle θ is between 36° and 37.5°.
[0055] The present application also provides a method for preparing a polarization beam splitter prism, which is used to prepare the polarization beam splitter prism. Figure 5 As shown, including:
[0056] S10: Wipe and clean the surface of the Glan prism to be plated, then place the Glan prism body 110 in a coating chamber of a coating machine, and evacuate and heat the coating chamber so that the temperature of the coating chamber is between 180-220° C.;
[0057] Before placing the Glan prism body 110 in the coating chamber, the Glan prism body 110 may be cleaned.
[0058] In order to make the temperature of the Glan prism body 110 reach 180-220°C, the temperature of the coating chamber can be maintained for 30 minutes after reaching the above temperature. -3 Pa.
[0059] S20: Cleaning the Glan prism body 110 by using an ion beam;
[0060] Specifically, oxygen plasma may be used to clean the Glan prism body 110 , with a cleaning time of 15-30 minutes and an oxygen flow rate of 15-25 sccm.
[0061] S30: forming a first low-refractive-index fluoride film 131, a first silicon oxide film 132, a first aluminum oxide film 133 and a second low-refractive-index fluoride film 134 in sequence on the first surface 111 of the Glan prism body 110;
[0062] The first low-refractive-index fluoride film 131 , the second low-refractive-index fluoride film 134 and the first silicon oxide film 132 are deposited by electron beam evaporation process; the first aluminum oxide film 133 can be deposited by electron beam evaporation reactive deposition process.
[0063] Specifically, the deposition rate of the low refractive index fluoride film is 0.4-1.0 nm / s, the deposition rate of the first silicon oxide film 132 is 0.4-0.8 nm / s, the deposition rate of the first aluminum oxide film 133 is 0.2-0.4 nm / s, and the oxygen filling flow rate is 10-25 sccm.
[0064] S40: Cooling down to room temperature in a high vacuum environment.
[0065] The above steps define the specific parameters and steps for forming the anti-reflection film on the first surface 111. The steps for setting the anti-reflection film on the second surface 114 and the third surface 113 are the same as those on the first surface 111, and are not described in detail here. Among them, the process parameters of the film layers with the same material are the same. In addition, the deposition rate of the hafnium oxide film is 0.15-0.3nm / s, and the oxygen filling flow rate is 30-50sccm.
[0066] In order to further verify the beneficial effects of the polarization beam splitter prism of the present application, the embodiment of the present application tests the residual reflectivity of the first surface 111, the second surface 114 and the third surface 113. The reflectivity of the first surface 111 can reach Rp<0.5%@(266-355)nm, the reflectivity of the polarization beam splitter surface 112 can reach Rp<1%@(266-355)nm, and the reflectivity of the third surface 113 can reach Rs<0.5%@(266-355)nm. The total transmittance and anti-laser damage threshold of the assembled polarization beam splitter prism are tested. The total transmittance of the polarization beam splitter prism can reach Tp>95%@(266-355)nm, and the anti-laser damage threshold can reach 2-3.2J / cm2@266nm, 10ns, 10Hz.
[0067] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A polarization beam splitter prism, characterized in that: The invention comprises a Glan prism body, wherein the Glan prism body comprises a first surface and a second surface arranged opposite to each other, a polarization splitting surface arranged between the first surface and the second surface, and a third surface arranged between the polarization splitting surface and the first surface or the second surface. Incident light enters the Glan prism body from the first surface and is separated at the polarization splitting surface to form P-polarized light and S-polarized light. The P-polarized light and the S-polarized light are emitted from the second surface and the third surface respectively. A first low-refractive-index fluoride film, a first silicon oxide film, a first aluminum oxide film and a second low-refractive-index fluoride film are sequentially arranged on the first surface as incident anti-reflection films.
2. The polarization beam splitter according to claim 1, characterized in that: The optical thickness ratio of the first low-refractive-index fluoride film, the first silicon oxide film, the first aluminum oxide film, and the second low-refractive-index fluoride film is (0.3-0.34):(1.43-1.47):(1-1.04):(0.94-0.98).
3. The polarization beam splitter prism according to claim 1, characterized in that: A P light anti-reflection film is arranged on the polarization splitting surface, and the P light anti-reflection film includes a third low refractive index fluoride film, a second aluminum oxide film, a fourth low refractive index fluoride film, a third aluminum oxide film, a fifth low refractive index fluoride film, a first hafnium oxide film and a sixth low refractive index fluoride film arranged in sequence.
4. The polarization beam splitter prism according to claim 3, characterized in that: The ratio of the optical thickness of the third low refractive index fluoride film, the second aluminum oxide film, the fourth low refractive index fluoride film, the third aluminum oxide film, the fifth low refractive index fluoride film, the first hafnium oxide film and the sixth low refractive index fluoride film is (0.48-0.52): (1.06-1.1): (0.48-0.52): (1-1.04): (1.21-1.25): (0.65-0.69): (0.28-0.32).
5. The polarization beam splitter prism according to claim 1, characterized in that: An S light anti-reflection film is disposed on the third surface, and the S light anti-reflection film includes a seventh low-refractive index fluoride film, a fourth aluminum oxide film, a second hafnium oxide film, and an eighth low-refractive index fluoride film disposed in sequence.
6. The polarization beam splitter prism according to claim 5, characterized in that: The optical thickness ratio of the seventh low-refractive-index fluoride film, the fourth aluminum oxide film, the second hafnium oxide film, and the eighth low-refractive-index fluoride film is (0.28-0.32):(1.72-1.76):(0.41-0.45):(1.19-1.23).
7. The polarization beam splitter prism according to any one of claims 1 to 6, characterized in that: The first low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the second low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the third low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the fourth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the fifth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the sixth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the seventh low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride; the eighth low refractive index fluoride film includes one of magnesium fluoride and aluminum fluoride.
8. The polarization beam splitter according to claim 3 or 5, characterized in that: The incident light is incident on the polarization splitting surface at an angle of θ, and the S-polarized light is incident on the third surface at an angle of 90°-2θ.
9. The polarization beam splitter according to claim 8, characterized in that: The angle θ is between 36° and 37.5°.
10. A method for preparing a polarization beam splitter prism, characterized in that: Used to prepare the polarization beam splitter prism according to any one of claims 1 to 9, comprising: Placing the Glan prism body in a coating chamber of a coating machine, and evacuating and heating the coating chamber so that the temperature of the coating chamber is between 180-220° C.; Use ion beam to clean the Glan prism body; A first low-refractive-index fluoride film, a first silicon oxide film, a first aluminum oxide film, and a second low-refractive-index fluoride film are sequentially formed on the first surface of the Glan prism body, wherein the first low-refractive-index fluoride film, the first silicon oxide film, and the second low-refractive-index fluoride film are prepared by electron beam evaporation process, and the first aluminum oxide film is plated by electron beam evaporation reaction deposition process; and the temperature is lowered to room temperature in a vacuum environment.
